Molecular diversity of citrus genotypes using callose synthase 7 gene markers linked to Huanglongbing resistance - Kristianto Nugroho; Agus Purwito; Dewi Sukma; Mia Kosmiatin; Tri Joko Santoso; Ali Husni; Chaireni Martasari; Puji Lestari (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
Huanglongbing (HLB), caused by Candidatus Liberibacter asiaticus, is a notable disease affecting citrus plantations globally. Several studies showed that the callose synthase 7 gene is crucial for the citrus defense system against this pathogen. The study aimed to analyze the nucleotide variations and genetic diversity among several citrus genotypes using specific gene primers designed from the callose synthase 7 gene sequence. Genomic DNA from eleven citrus genotypes was amplified using the specific primers, and Sanger sequencing was employed to identify the nucleotide sequence of the PCR products. The results revealed a total of 66 single-nucleotide polymorphisms (SNPs), 10 insertions, and 11 deletions were detected in callose synthase 7 gene fragment sequences. Of these, one out of five noteworthy SNPs identified at a position of 200 bp downstream of the START codon showed distinguishing features between susceptible and resistant/tolerant genotypes. Phylogenetic analysis clearly discriminated the eleven citrus genotypes into two clusters at a dissimilarity coefficient of 0.05, with all genotypes grouped in the first cluster, except for the Chinese box orange and orange jasmine. The identification of notable SNPs in this study can aid in developing new markers for the rapid selection of genotypes with enhanced HLB resistance in citrus breeding programs.   Keywords: Candidatus Liberibacter asiaticus; nucleotide variations; Sanger sequencing; phylogenetic analysis; SNP